Internet connectivity disruption in Tanzania (Tanzania) - Voidly (2026)
CRITICAL severity mixed detected in Tanzania. Confidence: 65%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: TZ-2026-0027
Keywords: censorship; TZ; mixed; critical